Late Jurassic Leucogranites of Macau (SE China): A Record of Crustal Recycling During the Early Yanshanian Orogeny - Shellnutt, J. Gregory; Vaughan, Matthew W.; Lee, Hao-Yang; Iizuka, Yoshiyuki (Frontiers in Earth Science, 2020)
The Yanshanian Orogeny consists of Jurassic to Cretaceous compressional-extensional cycles related to the subduction of the Paleo-Pacific Ocean beneath East Asia. Numerous granitic plutons were emplaced across southeast China at distinct intervals over a period of ~100 million years that migrate from the interior to the coast. A key region to help constrain the secular evolution of granitic magmatism related to the Yanshanian Orogeny is the Peal River estuary as three distinct Mesozoic magmatic belts congregate. The islands of Taipa and Coloane, Macau Special Administrative Region, are located along the western bank of the Pearl River estuary and are composed of spessartine-bearing biotite leucogranite. In situ zircon geochronology yielded Late Jurassic weighted-mean 206Pb/238U ages of 160.0 ± 2.0 Ma and 161.5 ± 2.0 Ma that correlate to the late Early Yanshanian Orogeny. Inherited zircons of Middle Triassic to Middle Jurassic age were also identified. The rocks are peraluminous, ferroan, calc-alkalic to calcic and classify as post-collisional granite. Geochemical modeling indicates that the chemical variability of the rocks is related to hydrous fractional crystallization under reducing conditions (dFMQ -1) at ~7 km depth. The Sr-Nd isotopes (ISr = 0.71156 to 0.72477; eNd(t) = -7.9 to –8.6), zircon Hf isotopes (eHf(t) = -3.8 to -8.8), incompatible trace element ratios, and whole rock composition indicate that the parental magma was derived primarily from a sedimentary source. It is likely that the islands of Taipa and Coloane form a coherent plutonic complex that may be a member of larger batholith that extends across the Pearl River estuary to Hong Kong. The emplacement of the leucogranites is attributed to decompressional melting associated with a period of crustal relaxation or tensional plate stress that occurred during the transition from low angle subduction to high angle subduction of the Paleo-Pacific plate.